ANALISIS RESTRUKTURISASI ORGANISASI DAN PENERAPAN E-SYSTEM TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK - Margareth Setyorini (LPPM STIE YAPAN, 2020)
Weakness of tax administration led to a less than optimal tax revenue, therefore, the government made some efforts to improve, one of which is the implementation of the modernization of tax administration. The purpose of this study was to determine whether administration modernization have influenced and contributed to employee satisfaction KPP Mulyorejo, Surabaya. This research is in the positivist paradigm by using a quantitative approach. Object of study is a personnel numbering KPP Mulyorejo sample of 84 people and 35 employees. Partial Least Square (PLS) is a method of analysis is a powerful and predictive models that PLS is an appropriate tool to prove the hypothesis. The results proved that the whole hypothesis is accepted. Modernization of tax administration which consists of the modernization of the organizational structure and modernization of information technology, which has contributed to satisfaction is the information technology modernization, while modernizing the organizational structure has no contribution